Combined action observation and motor imagery facilitates visuomotor adaptation in children with developmental coordination disorder. (March 2020) - Marshall, B.; Wright, D.J.; Holmes, P.S.; Williams, J.; Wood, G.
Highlights: Combined action observation and motor imagery facilitates visuomotor adaptation. Updating of the internal forward model can be advanced by an AO + MI intervention. Internal modelling deficits in children with DCD are reflected in their eye-movements. AO + MI intervention improved eye-hand coordination and movement kinematics. AO + MI has potential as an intervention technique for use with children with DCD. Abstract: The internal modelling deficit (IMD) hypothesis suggests that motor control issues associated with Developmental Coordination Disorder (DCD) are the result of impaired predictive motor control. In this study, we examined the benefits of a combined action observation and motor imagery (AO + MI) intervention designed to alleviate deficits in internal modelling and improve eye-hand coordination during a visuomotor rotation task. Twenty children with DCD were randomly assigned to either an AO + MI group (who watched a video of a performer completing the task whilst simultaneously imagining the kinaesthetic sensations associated with action execution) or a control group (who watched unrelated videos involving no motor content). Each group then attempted to learn a 90° visuomotor rotation while measurements of completion time, eye-movement behaviour and movement kinematics were recorded. As predicted, after training, the AO + MI group exhibited quicker completion times, more target-focused eye-movement behaviour and smoother movement kinematics compared to the control group. No significant after-effects were present. These results offer further support for the IMD hypothesis and suggest that AO + MI interventions may help to alleviate such deficits and improve motor performance in children with DCD.